Increasing Crude Protein Content of Sago Dregs Through Solid State Fermentation Process - Syahiddin Dahlan Said; Komala Pontas; Anwar Thaib; T. Maimun; Cut Silvianti; Ayi Ansarmina (Journal of Applied Technology, 2022)
Increasing the protein content in sago dregs aims to increase its nutritional value so that it is more useful as animal feed. Increasing protein in sago dregs was carried out by solid state fermentation using Trichoderma reesei bioconversion agent. Fermentation process variables considered in this study were fermentation time (0, 2, 4, 6, 8, 10 days), substrate moisture content (50, 60, 70, and 80%), substrate C/N ratio (10:1, 20:1, 30:1, and 40:1), and the molasses content in the substrate (20, 30, 40, and 50%). The optimum conditions for the fermentation process were obtained at: 6 days fermentation time, 20:1 C/N ratio, and 50% substrate moisture content. Under optimum conditions, the fermentation process with a substrate containing 20% and 50% molasses resulted in a protein content of 18, 4 and 31% (product dry weight).